2014
DOI: 10.1051/fruits/2014023
|View full text |Cite
|
Sign up to set email alerts
|

Crop productivity, yield and seasonality of breadfruit (Artocarpusspp., Moraceae)

Abstract: Crop productivity, yield and seasonality of breadfruit (Artocarpus spp., Moraceae).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…It is now being recognized for its potential to positively impact hunger in the tropics and developing world (Jones et al, 2013a&b). A single breadfruit tree produces 200-400 kg or more of fruit per year (Jones et al, 2011b;Liu et al, 2014) and can be cooked and eaten in many different ways. Fruits can be roasted, boiled, dried, pickled, fermented or used in bread making.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now being recognized for its potential to positively impact hunger in the tropics and developing world (Jones et al, 2013a&b). A single breadfruit tree produces 200-400 kg or more of fruit per year (Jones et al, 2011b;Liu et al, 2014) and can be cooked and eaten in many different ways. Fruits can be roasted, boiled, dried, pickled, fermented or used in bread making.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The National Tropical Botanical Garden in Hawaii has assembled an accessioned, curated collection of more than 300 mature trees representing more than 120 distinct cultivars and all of the closely related species with plant material originating from 34 Pacific islands, the Seychelles, Indonesia, the Philippines and Honduras (Liu et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The breadfruit tree is fast-growing and produces an abundance of nutritious starchy fruit [10][11][12]. These trees are reported to produce 6 t-ha −1 of fruit that is rich in carbohydrates, amino acids, fiber, vitamins, and minerals, including micronutrients such as iron and potassium, especially when compared to other tropical staple starch crops such as cassava, sweet potato and banana [2,10,[13][14][15][16][17]; however, exact fruit yield estimations are variable due to seasonality, cropping systems, cultivar and environment [11]. A study by Liu et al reported that, on average, between 24 breadfruit cultivars, 269 fruits per year were produced, with each fruit weighing an average of 1.2 kg [17].…”
Section: Introductionmentioning
confidence: 99%
“…These trees are reported to produce 6 t-ha −1 of fruit that is rich in carbohydrates, amino acids, fiber, vitamins, and minerals, including micronutrients such as iron and potassium, especially when compared to other tropical staple starch crops such as cassava, sweet potato and banana [2,10,[13][14][15][16][17]; however, exact fruit yield estimations are variable due to seasonality, cropping systems, cultivar and environment [11]. A study by Liu et al reported that, on average, between 24 breadfruit cultivars, 269 fruits per year were produced, with each fruit weighing an average of 1.2 kg [17]. Therefore, it is evident that breadfruit has the potential to target issues surrounding food and nutrition security if specific cultivars and growing conditions are optimized [13,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…A broad range of yields are reported for breadfruit, from 25 to over 2000 kg per tree (Lincoln et al, 2018), but the majority of studies are anecdotal and based on broad estimations using fruit counts over a short period, with few systematic yield analyses. Liu et al (2014) demonstrate that, in Hawai'i, most varieties produced fruit 4 yr after planting, with an average of 47 ± 8 fruit produced by the young trees, increasing to 130 ± 22 fruit per tree after 7 yr and continuing to increase throughout the study. Measurements indicate differences in net primary productivity potential, such as SPAD and leaf intersection, which has been shown to correlate to productivity in other crop species (e.g., Charbonnier et al, 2017; Madugundu et al, 2017) and in breadfruit (Lincoln et al, 2019).…”
Section: Discussionmentioning
confidence: 98%